Serum-free light chain test utilisation at a South African academic laboratory and comparison with serum protein electrophoresis results - Razia B. Banderker; Fatima B. Fazel; Annalise E. Zemlin; Aye-Aye Khine; Thumeka P. Jalavu (AOSIS, 2023)
Background: Serum protein electrophoresis (SPE), urine protein electrophoresis and immunofixation electrophoresis were traditionally utilised for the diagnosis of monoclonal gammopathies. The quantitative serum-free light chain (SFLC) assay is reportedly more sensitive and has been introduced to recent clinical guidelines. Objective: This study aimed to investigate SFLC test utilisation and describe SPE findings in patients with abnormal SFLC ratios. Methods: A retrospective audit of SFLC analyses was conducted in Cape Town, South Africa, from May 2018 to April 2020. Agreement between abnormal SFLC ratios and SPE results was determined in a sub-group of patients screened for monoclonal gammopathies. Serum-free light chains were analysed using Freelite® Kappa and Lambda assays. Results: Of the 1425 patients included in the audit, 741 (52%) had abnormal SFLC ratios; 636 (45%) had increased and 105 (7%) had decreased SFLC ratios. In a sub-group analysis of 117 new patients with an abnormal SFLC ratio, 57 had a monoclonal protein (M-protein) on SPE (49%), and 60 (51%) did not. Four out of 60 patients without M-protein had a plasma cell dyscrasia, while renal impairment or inflammatory response accounted for the rest. Of the 57 patients with a M-protein and abnormal SFLC ratio, 41 (72%) had a plasma cell dyscrasia, seven (12%) had lymphomas and nine patients (16%) were unclassifiable. Conclusion: Serum-free light chains should be requested when there is a high index of clinical suspicion. Neither SFLC nor SPE should be performed in isolation when screening patients for monoclonal gammopathy, to ensure that no patient is missed. What this study adds: The study adds to the evidence on SFLC test utilisation. Serum protein electrophoresis alone may miss cases of light chain myeloma, while SFLC performed in isolation may produce false positive results in the setting of inflammatory disorders or renal impairment, leading to unnecessary further investigation.